Pengaruh Model Pembelajaran TPSR Terintegrasi Fitness Education terhadap Peningkatan Keterampilan Bermain Sepak Bola dan Keterampilan Sosial pada Anak Sekolah Dasar - Rivaldi Mahendra Wuliyanto; Agus Mahendra; Achmad Syakur Fahri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the effect of the Teaching Personal and Social Responsibility (TPSR) learning model integrated with Fitness Education on the soccer playing skills and social skills of elementary school students compared to conventional learning. The study used a quantitative approach with a quasi-experimental method and a nonequivalent pretest-posttest control group design. The study sample consisted of 40 fifth-grade students at SDN 062 Ciujung, Bandung City, divided into an experimental group and a control group. The instruments used were the Game Performance Assessment Instrument (GPAI) to measure soccer playing skills and the Social Skills Improvement System (SSIS) to measure social skills. Data were analyzed using a normality test, followed by the Wilcoxon Signed-Rank Test and the Mann-Whitney U test due to non-normal distribution. The results showed a significant difference between the pretest and posttest scores in both groups (p = 0.01 < 0.05). Furthermore, the Mann-Whitney U test showed significant differences between the experimental and control groups in soccer skills (p = 0.01) and social skills (p = 0.03). These findings indicate that the TPSR learning model integrated with Fitness Education has a greater impact than conventional learning in improving soccer skills and social skills in elementary school students. Therefore, the TPSR learning model integrated with Fitness Education can be used as an alternative educational learning method to develop both motor skills and social skills in students. Keywords: Elementary School, Fitness Education, Soccer Skills, Social Skills, Teaching Personal And Social Responsibility (TPSR).